Juliane’s Speech: Knut Hamsun’s Play «Livet ivold» - Zagar, Monika (Nordlit, 2003)
My article will present an examination of interactional styles in dialogues created by Knut Hamsun in his 1910 play In the Grip of Life (Livet i vold). Hamsun equipped his protagonists with a particular speech. The point of the analysis is to investigate how Hamsun fleshed out his protagonists' speech styles, what he deemed as the most suitable and appropriate speech for women and men, and how he lets them transgress it. In fact, Hamsun uses transgression of the traditional rules of gender communication as his creative technique. Following Weber-Knapp's strategy, my analysis will focus on the following: length and frequency of speech contributions, interruptions, and initiating and responding utterances